SNP-Profiles of Yersinia pestis Strains of the Medieval Biovar from the Caspian Sea Region Plague Foci - A. N. Balykova; L. M. Kukleva; P. A. Goryunova; K. S. Shevchenko; A. V. Kovrizhnikov; Ya. M. Krasnov; N. S. Chervyakova; G. A. Eroshenko; V. V. Kutyrev (Проблемы особо опасных инфекций, 2023)
The SNP-typing method based on the detection of stable genetic markers in the genome, i.e., single nucleotide polymorphisms, is successfully used for genotyping of pathogenic microorganisms and can be applied for SNP-profiling of Yersinia pestis strains and molecular-genetic certification of focal areas. The aim of the study was to determine the SNP profiles of Y. pestis strains of the medieval biovar isolated in the Caspian Sea region plague foci in 1912–2015 and to develop a method for identifying unique SNPs using the Sanger sequencing for molecular-genetic certification of these territories. Materials and methods. A comprehensive study of the phenotypic and genotypic properties of 190 Y. pestis strains from plague foci in the Caspian Sea region was carried out. Phylogenetic reconstruction by the Maximum Likelihood method (GTR model) in the SeaView 5.0.4 software was performed on the basis of 1621 SNPs identified among 50 Y. pestis strains according to WG-SNP analysis in the snippy 4.6 program. Primers for PCR amplification of the SNP loci selected as target were calculated using the Vector NTI program. Sanger sequencing of SNPs loci was conducted on an ABI PRISM 3500XL genetic analyzer (Applied Biosystems, USA). Results and discussion. According to phenotypic characteristics, all studied strains from the Caspian foci belonged to a highly virulent and epidemically significant medieval biovar of the main subspecies of Y. pestis. According to the results of the WG-SNP analysis, 9 SNP genotypes were identified based on the polymorphism of single nucleotides of 24 genes characteristic of the main phylopopulations, which include strains isolated during various periods of epidemic and epizootic activity in the Caspian plague foci. Determining of SNP genotypes of Y. pestis strains of the medieval biovar, obtained over a hundred years in the Caspian foci, creates the prerequisites for defining the canonical SNP profile (canSNP) and for developing an algorithm for molecular epidemiological monitoring of the foci in which this highly virulent biovar circulates.